Teknik Konseling Terpadu untuk Meningkatkan Kualitas Pengasuhan Keluarga - Hidayat, Dian Roslan (Jurusan Bimbingan dan Konseling Islam, 2018)
The research was motivated by empirical facts about the symptoms of decline in the quality of parenting who indicated the need for family counseling services. The research objective is: to know the quality of parenting before and after the counseling is done, to formulate an integrative model of family counseling techniques as outlined in the module guide operational techniques, and to test the effectiveness of integrative family counseling techniques in improving the quality of parenting. This research method applied the research and development. Method development carried out to formulate an integrative family counseling technique proven its effectiveness to improve the quality of parenting. The method of research applied quantitative research methods quasi-experimental research design with nonequivalent control group design. The results showed the quality of parenting counseling prior to the experimental group on average at a good level, with some quality family is middle quality. The results after counseling the entire family performed the experimental group showed an average of good quality, with some families are very good quality. The results showed an integrative model of family counseling techniques to improve the quality of parenting as feasible and tested its effectiveness.